2020
DOI: 10.1080/09540962.2020.1748855
|View full text |Cite
|
Sign up to set email alerts
|

New development: ‘Healing at a distance’—telemedicine and COVID-19

Abstract: In extreme circumstances such as pandemics, the presence of patients in hospital emergency departments becomes untenable. Healthcare professionals and organizations worldwide are leaning on technology as a crucial ally to deal with the COVID-19 outbreak. This article focuses on the positive impact of telemedicine for helping service provision, from enabling virtual triage to mitigating the negative psychological effects of social isolation. The authors discuss the challenges and opportunities to telemedicine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(204 citation statements)
references
References 11 publications
2
179
0
8
Order By: Relevance
“…Connected digital devices enable both remote work and education. Additionally, chatbots are providing instant life-saving information, partially relieving overwhelmed health systems (Leite et al, 2020). Further, geolocation information systems are helping health workers and researchers to track and map the spread of the virus.…”
Section: Cluster 2c: Covid-19 and Emerging Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Connected digital devices enable both remote work and education. Additionally, chatbots are providing instant life-saving information, partially relieving overwhelmed health systems (Leite et al, 2020). Further, geolocation information systems are helping health workers and researchers to track and map the spread of the virus.…”
Section: Cluster 2c: Covid-19 and Emerging Technologiesmentioning
confidence: 99%
“…The public health emergency of COVID-19 confronting global healthcare systems has prompted the development of digital health solutions to mitigate the impact of the pandemic (Panigutti et al, 2020). These digital healthcare systems include telehealth; robust surveillance systems; technology-driven diagnostic and clinical decisionmaking tools; wearable tracking devices to measure physiological parameters like temperature, heart rate, and sleep-duration; and interactive chat services providing information about COVID-19 (Leite et al, 2020). Telemedicine administered through virtual chatbots and webbots is emerging as a viable option for communication and safe medical care.…”
Section: Cluster 2d: Covid-19 and Digital Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…However, social distancing brings fear of uncertainty, physical discomfort, loneliness, anxiety, and stress (Xiang et al, 2020) that negatively affect the teaching-learning process at university. The prolonged social distancing creates loneliness, anxiety, depression, and even mental disorder (Leite et al, 2020;Karen & Cathy, 2020). The major problems emerged unexpectedly such as violence, racial and ethnical prejudice, environmental and technological disaster have important psychological aspects to the students (Lerner et al, 2020) and the lifestyle of students have been affected because of fear due to COVID-19 pandemic and Nepalese students are no exception.…”
Section: Reviews Of Teaching Learning-related Research During Pandemicmentioning
confidence: 99%
“…However, the psychological impact of quarantine to students is wide-ranging (Brooks et al, 2020). The prolonged closure of college and students home confinement obviously would harm physical and mental health (Leite et al, 2020). A study found that the COVID-19 pandemic is deemed as a threat, causes fear, anxiety, and uncertainty (Ling & Ho, 2020).…”
Section: Reviews Of Teaching Learning-related Research During Pandemicmentioning
confidence: 99%